2019
DOI: 10.1002/fsn3.918
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of Moringa oleifera leaf on reproductive performance in mice

Abstract: Moringa oleifera is a tropical plant with high nutritional and medicinal value. Recent studies have reported its remarkable effects in inflammatory, antioxidative, and anti‐diabetes modulations, but there was no significant report on its role in animal breeding. In this study, we investigated the effects of dietary Moringa oleifera leaf (MOL) on reproductive performances in mice. We studied the reproductive performance of mice for six consecutive gestations. Mice fed with 4% MOL diet showed improved litter siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
(40 reference statements)
3
19
0
Order By: Relevance
“…Generally, the obtained findings in the present study regarding the serum biochemical parameters demonstrated that dietary SP had no harmful effect on adult rabbits' reproductive physiology performance. Similarly, with the current findings no negative effects on the reproductive performance of mice fed-MOL have been reported by Zeng et al (2019). These positively effects of dietary SP on serum biochemistry traits of treated rabbits in the current study due to its known as a powerful antioxidant in herbal supplements, as well as its contents phycocyanin, tocopherols, beta carotene and vitamin C are in progress of growth and health status of experimental animals (Karkos et al, 2011;Abdel-Daim et al, 2013;Seyidoglu et al, 2019).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Generally, the obtained findings in the present study regarding the serum biochemical parameters demonstrated that dietary SP had no harmful effect on adult rabbits' reproductive physiology performance. Similarly, with the current findings no negative effects on the reproductive performance of mice fed-MOL have been reported by Zeng et al (2019). These positively effects of dietary SP on serum biochemistry traits of treated rabbits in the current study due to its known as a powerful antioxidant in herbal supplements, as well as its contents phycocyanin, tocopherols, beta carotene and vitamin C are in progress of growth and health status of experimental animals (Karkos et al, 2011;Abdel-Daim et al, 2013;Seyidoglu et al, 2019).…”
Section: Resultssupporting
confidence: 86%
“…Similarly, significant enhancement in litter weight and size at birth of NZW rabbit bucks fed red algae compared to the control group were detected by Ali and Ghazal (2013). Recently, Zeng et al (2019) also stated that dietary Moringa oleifera leaf (MOL) was able to improve litter size, litter birth weight, and litter survival of weaning mice. In general, the reproductive efficacy of rabbits depends on semen quality of bucks, the physiological status of the does, and the environmental aspects (Theau-Clement and Roustan, 1992).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The basal diet consisted of wheat, corn, rice bran, soybean meal, sugarcane molasses, and minerals formulated to fulfill the nutritional requirements of the goats (19) as shown in Table 1. The feeding levels were adjusted according to the previous studies conducted on mice with some modification in the goats (17,20). The does were offered free pasture (Chloris gayana, Carduus nutans, Leptochloa fusca, Cirsium arvense, and Chenopodium album) grazing two times during the morning and evening schedule and were provided free access to clean drinking water.…”
Section: Study Design and Animal Managementmentioning
confidence: 99%
“…The MO has been reported to improve reproductive performance and serum antioxidant status during pregnancy in mice (17). Previous studies provided information about the impact of MO on lactation performance and milk quality in dairy cows and goats (9,18).…”
Section: Introductionmentioning
confidence: 99%